PENERAPAN HUKUM KIRCHOFF PADA RANGKAIAN EKUIVALEN UNTUK MEMPEROLEH PERSAMAAN TELEGRAF - Maria D. L. Rumlus; Tri Widjajanti; Rium Hilum (Jurnal Natural, 2020)
Telegraph is a machine for sending and receiving messages remotely. Telegraph according to Zauderer can be modeled or expressed in mathematical language, namely the telegraph equation. Kirchoff I's Law deals with currents and Kirchoff II's Law is the basis for analyzing all electrical circuits. The purpose of this research is to apply Kirchoff's Law to obtain the telegraphic equation. The stages in research include: determining the equivalent circuits, making assumptions, applying Kirchoff's Laws I and II to the equivalent circuits, and forming telegraphic equations. The results of this study are to obtain a telegraphic equation which is a partial differential equation with general forms